Integrasi Filsafat Ilmu Pengetahuan dan Studi Islam: Analisis Kritis Konsep Ilmu Pengetahuan - Putra, Ronika; Kamal, Tamrin; Hakim Hanafi, Abdul (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
The integration of the philosophy of science and Islamic studies presents fertile ground for reexamining the concept of science from a holistic perspective. This journal article critically analyzes the intersection between these two domains, aiming to reveal how philosophical principles can enrich Islamic epistemology and methodology. By exploring the historical evolution of science in Islamic civilization and its philosophical foundations, this study highlights the enduring relevance of classical Islamic scholarship in contemporary scientific discourse. This analysis investigates key philosophical concepts such as epistemology, ontology, and methodology, and examines their implications for Islamic studies. Furthermore, this article discusses the challenges and opportunities of integrating Western scientific paradigms with Islamic thought, proposing a framework for a more comprehensive and inclusive understanding of science. Through a critical review of existing literature and original theoretical contributions, this study underscores the need for dialogue between the philosophy of science and Islamic studies, advocating a new appreciation of the intellectual heritage that can inform and enhance modern scientific endeavors in an Islamic context.